Case Study New design 3 Blades Type on 35 Developed Area and Testing cavitation of Tailing Thai Boat - Jaruphant Noosomton; Jarruwat Charoensuk (My University, 2015)
This paper presents to case study new design of propeller 3 blade types and focus cavitation flow around ship propellers experimentally. Testing of different types new model propellers and local type propellers are performed in this study. A 3-blades, skew angle 22 degree, developed area 35 which call Model-A (B3-22-35) and comparison which local type propeller commonly used by Thai fishermen. A practical design method was achieved by combining a vortex lattice lifting method and lifting surface method. The optimum circulation distribution yielding the maximum lift-to-torque ratio was computed for given thrust and chord lengths along the radius of the propeller by dividing the blade into a number of panels extending from hub to tip. The radial distribution of bound circulation could be computed by a set of constant-strength vortex elements. The cavitaion phenomenon of new design appeared to be less than local type.
Keywords: Chord (peer-to-peer); Lift (data mining); Cavitation Phenomena in Pumps